Thermodynamics of intercalated layer crystals at low temperatures - Tovstyuk, N.K. (Condensed Matter Physics, 2001)
On the base of Anderson type model the density of electron states in the intercalated layer crystal is obtained. Thermodynamic stability depending on: band width, lamination degree, intercalant energy state and renormalized electron mixing, caused by intercalation, is analyzed.